Three new species of the genus Philagra Stål (Hemiptera: Cercopidea: Aphrophoridae) from China and Bangladesh - Liang, Ai-Ping (Zootaxa, 2022)
Three new species of Philagra Stål, P. bimaculata sp. nov., P. fuscofasciata sp. nov. and P. straminea sp. nov. are described and illustrated from China with P. bimaculata sp. nov. also recorded from Bangladesh. Morphological descriptions and structural illustrations of the new species are provided with distributional data given. Scanning electron micrographs of antennal sensilla of P. bimaculata sp. nov. and P. straminea sp. nov. and sensilla on rostral apex of P. bimaculata sp. nov. are provided for the first time.